HEPATOSPLENIC ΑΒ T-CELL LYMPHOMA WITH ISOCHROMOSOME 7Q AND TRISOMY 8: A RARE DIAGNOSTIC CHALLENGE WITH CYTOGENETIC CONFIRMATION ASSOCIATED WITH RAPID DISEASE PROGRESSION AND HIGH MORTALITY (Asian Journal of Medical Research and Health Sciences, 2026)
Background:An uncommon and extremely aggressive form of peripheral T-cell lymphoma, HSTCL (Hepatosplenic T-Cell Lymphoma) is distinguished by extranodal involvement of the liver, spleen, and bone marrow. It is linked to a poor prognosis and makes up less than 5% of peripheral T-cell lymphomas. Case Presentation: A 33-year-old male presented with a three-month history of fever, recurrent epistaxis, pancytopenia, and massive splenomegaly. Initial bone marrow examination demonstrated dysplastic changes suggestive of myelodysplastic syndrome. Flow cytometric immunophenotyping subsequently identified a clonal CD8-positive αβ T-cell population expressing CD2, CD3, CD7, CD16, CD38, and CD94 with TRBC1 restriction. Cytogenetic analysis revealed isochromosome 7q and trisomy 8, characteristic abnormalities associated with hepatosplenic T-cell lymphoma. The patient received CHOP-E-based chemotherapy and multiple transfusions for severe cytopenias. Despite prompt initiation of timely treatment, he succumbed to progressive disease, again highlighting the aggressive biology and poor prognosis of the disease . Conclusion: HSTCL should be considered in young patients presenting with unexplained pancytopenia, hepatosplenomegaly, and absence of significant lymphadenopathy. Early utilization of flow cytometry and cytogenetic studies may facilitate timely diagnosis of this aggressive malignancy.